Clothing of the Kazan tatars in the artworks of M.K. Tilke: revisiting the representation of a visual source - D. F. Gatina-Shaﬁkova (Вестник Майкопского государственного технологического университета, 2024)
An artwork as a scientiﬁc unit in the study of the works of M.K. Tilke is an important source category when studying the material aspects of the Tatar heritage. The goal of the research is to study, systematize and introduce visual sources that reproduce the costume complex of the Tatars into scientiﬁc circulation. During the research the following tasks were solved: certain types of clothing reproduced in sketches were identiﬁed and described; graphic, written sources and surviving material heritage in museum collections were analyzed. The method of historical and ethnographic research was used. The conclusions: each of the artist’s artworks is ethnographically accurate, since the main goal was to reveal the uniqueness, signiﬁcance and features of the costume complex. Participation in scientiﬁc expeditions, consistent study and comparison of graphic, written sources and preserved material heritage in museum collections revealed an accurate reproduction of the cut features. As a researcher, he tried to draw parallels with other peoples, those close in culture, or simply those in interaction with the Tatars. Turning to early historical and ethnographic sources, M. Tilke tried to identify the general and speciﬁc in the details of the Tatar women's and men's costume complex.